Medication Adherence and Compliance: Recipe for Improving Patient Outcomes - Taiwo Opeyemi Aremu; Oluwatosin Esther Oluwole; Kehinde Oluwatosin Adeyinka; Jon C. Schommer (MDPI AG, 2022)
The indices of patients' health outcomes have historically included recurrence of symptoms, number of emergency visits, hospitalization and re-admission rates, morbidity, and mortality. As significant healthcare players, providers can influence these events, including the timeliness of diagnosis and disease management, the cost of treatment, access to health insurance, and medication adherence. Beyond healthcare availability and access, the ability of patients to adhere to providers' treatment recommendations goes a long way to serve as a recipe for improving patient outcomes. Unfortunately, medication nonadherence has been prevalent, culminating in worsened health conditions, increased cost of care, and increased healthcare spending. This article provides some innovative ideas and good considerations for encouraging medication adherence. Improving providers' and patients' education and adopting active and passive communication, including consented reminders, could enhance compliance. Embracing partnerships between providers' organizations and faith-based and community organizations could drive adherence. Adopting an income-based cap on out-of-pocket spending and adapting the physical properties, bioavailability, and dosage regimen of medications to accommodate diverse patient population preferences could encourage refills and compliance. Good medication adherence can culminate in improved patient outcomes.